Ossification of the Anterior Longitudinal Ligament with Dysphagia as the First Symptom: Rehabilitation of Two Cases - Norihiro Nishida; Hiroyoshi Ogasa; Kazushige Seki; Tomohiro Kato; Yasuaki Imajo; Hidenori Suzuki; Masahiro Funaba; Kiminori Yukata; Takashi Sakai (Applied Sciences, 2021)
Dysphagia is associated with poor quality of life, and pneumonia due to aspiration is life-threatening. Cervical ossification of the anterior longitudinal ligament (C-OALL) is one of the causes of dysphagia, and we report two cases in which dysphagia improved after surgery. Case 1: A 76-year-old man had C-OALL of greater than 16 mm and dysphagia and developed myelopathy. A fall resulted in upper and lower limb insufficiency paralysis, and posterior decompression fixation was performed. Pressure on the pharynx by C-OALL remained, but dysphagia improved. Improvement in this case was considered to be due to the loss of intervertebral mobility. Case 2: A 62-year-old man developed dysphagia 6 years ago. It gradually exacerbated, and the C-OALL increased. Laryngeal fiberscope and swallowing angiography revealed that the pharyngeal cavity was compressed and narrowed anteriorly due to ossification. Resection of the ossification was performed, and the patient’s symptoms improved. Direct decompression was successful in this case. Several evaluation methods for dysphagia have been reported, including screening tests, endoscopy, contrast studies, and radiological evaluation. In case 1, extensive ossification was improved by posterior fixation, albeit incidentally, whereas in case 2, a patient with extensive ossification exhibited symptoms. It is necessary to examine the cervical mobility, extent and morphology of ossification, and timing of surgery stenosis to determine the risk factors and treatment options, including rehabilitation.